Pengaruh Dosis Pupuk Kandang Ayam dan Konsentrasi Eco-Enzyme terhadap Pertumbuhan dan Produksi Tanaman Kacang Panjang (Vigna sinensis L.) - Yelfi Yana Linda Br Jabat; Beatrix Sofranes Napitupulu; Ari Permana Ginting (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Abstract. Long beans are one of the horticultural crops that have high economic value and play an important role in meeting the food and nutritional needs of the community. One of the efforts developed to increase the growth and production of long beans is the administration of chicken manure doses combined with eco-enzyme concentrations. This study aims to determine the dose of chicken manure and eco-enzyme concentration in increasing the growth and production of long beans (Vigna sinensis L.). The study was conducted in March 2024 at the Experimental Garden of the Faculty of Agriculture, Indonesian Community Development University (UPMI) Medan using a factorial Randomized Block Design (RAK) with two factors, namely the dose of chicken manure (0, 20, 40, and 80 tons/ha) and the concentration of eco-enzyme (0, 10, 20, and 30 ml/L of water) with three replications. The parameters observed included plant height at 14-35 days after planting (DAP) and pod weight per sample at the end of the observation. The results of the analysis of variance showed that neither the chicken manure dosage nor the eco-enzyme concentration significantly affected plant height and pod weight per long bean sample. Furthermore, there was no significant interaction between the two treatments for any of the observed parameters. This study indicates that under the research conditions, neither the chicken manure dosage nor the eco-enzyme concentration used at the doses used were able to significantly increase long bean growth and production. Therefore, further studies regarding dosage, application time, and soil conditions are needed to obtain a more optimal plant response. Keywords: eco-enzyme, long bean, chicken manure fertilizer, growth, production